SIRT1 inactivation switches reactive astrocytes to an antiinflammatory phenotype in CNS autoimmunity - Weifeng Zhang; Dan Xiao; Xing Li; Yuan Zhang; Javad Rasouli; Giacomo Casella; Alexandra Boehm; Daniel Hwang; Larissa L.W. Ishikawa; Rodolfo Thome; Bogoljub Ciric; Mark T. Curtis; et al. (The Journal of Clinical Investigation, 2022)
Astrocytes are highly heterogeneous in their phenotype and function, which contributes to CNS disease, repair, and aging; however, the molecular mechanism of their functional states remains largely unknown. Here, we show that activation of sirtuin 1 (SIRT1), a protein deacetylase, played an important role in the detrimental actions of reactive astrocytes, whereas its inactivation conferred these cells with antiinflammatory functions that inhibited the production of proinflammatory mediators by myeloid cells and microglia and promoted the differentiation of oligodendrocyte progenitor cells. Mice with astrocyte-specific Sirt1 knockout (Sirt1–/–) had suppressed progression of experimental autoimmune encephalomyelitis (EAE), an animal model of CNS inflammatory demyelinating disease. Ongoing EAE was also suppressed when Sirt1 expression in astrocytes was diminished by a CRISPR/Cas vector, resulting in reduced demyelination, decreased numbers of T cells, and an increased rate of IL-10–producing macrophages and microglia in the CNS, whereas the peripheral immune response remained unaffected. Mechanistically, Sirt1–/– astrocytes expressed a range of nuclear factor erythroid–derived 2–like 2 (Nfe2l2) target genes, and Nfe2l2 deficiency shifted the beneficial action of Sirt1–/– astrocytes to a detrimental one. These findings identify an approach for switching the functional state of reactive astrocytes that will facilitate the development of astrocyte-targeting therapies for inflammatory neurodegenerative diseases such as multiple sclerosis.